PENINGKATAN KETERAMPILAN MENULIS TEKS ARGUMENTASI MENGGUNAKAN MEDIA KARTU BERPASANGAN PADA PESERTA DIDIK KELAS XI SMA NEGERI 3 MEDAN - Namira, Suci; Srikandi, Cut Novita; Simarmata, Natalia (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The purpose of this study was to assess how much students of grade XI at SMA Negeri 3 Medan can improve their ability in writing argumentative texts by using paired cards as an aid. This study involved thirty-six students in grades XI–1-2. Quantitative and qualitative methods were used in the analysis of learning outcomes. This study was conducted in two cycles, cycle I and cycle II, including planning, action, observation, and reflection in each cycle. Observations during cycle I revealed that students had difficulty in creating argumentative texts, as evidenced by their average score of 79.47 and their classical completeness of only 63.84%. Cycle II showed an increase with an average score of 91.12 and classical completeness of 94.45% after introspection and improvement. The results of the study showed the benefits of paired cards media on students' ability to write argumentative texts, and it was proven that this approach was effective in the process of learning Indonesian.